Ductility Evaluation of As-Hydrided and Hydride Reoriented Zircaloy-4 Cladding under Simulated Dry-Storage Condition. Issue 1645 (2014) - Yan, Y.; Plummer, L. K.; Ray, H.; Cook, T.; Bilheux, H. Z.
ABSTRACT: Pre-storage drying-transfer operations and early stage storage expose cladding to higher temperatures and much higher pressure-induced tensile hoop stresses relative to normal operation in-reactor and pool storage under these conditions. Radial hydrides precipitate during cooling and could provide an additional embrittlement mechanism as the cladding temperature decreases below the ductile-to-brittle transition temperature. To simulate this behavior, unirradiated Zircaloy-4 samples were hydrided by a gas charging method to levels that encompass the range of hydrogen concentrations observed in current used fuel. Mechanical testing was carried out by the ring compression test (RCT) method at various temperatures to evaluate the sample's ductility for both as-hydrided and post-hydride reorientation treated specimens. As-hydrided samples with higher hydrogen concentration (>800 ppm) resulted in lower strain before fracture and reduced maximum load. Increasing RCT temperatures resulted in increased ductility of the as-hydrided cladding. A systematic radial hydride treatment was conducted at various pressures and temperatures for the hydrided samples with H content around 200 ppm. Following the radial hydride treatment, RCTs on the hydride reoriented samples were conducted and exhibited lower ductility compared to as-hydrided samples.